Stability and excitation dynamics of an argon micro-scaled atmospheric pressure plasma jet. (17th November 2015) - Dünnbier, M; Becker, M M; Iseni, S; Bansemer, R; Loffhagen, D; Reuter, S; Weltmann, K-D
Abstract: A megahertz-driven plasma jet at atmospheric pressure—the so-called micro-scaled atmospheric pressure plasma jet ( μ APPJ)—operating in pure argon has been investigated experimentally and by numerical modelling. To ignite the discharge in argon within the jet geometry, a self-made plasma tuning unit was designed, which additionally enables measurements of the dissipated power in the plasma itself. Discharges in the α -mode up to their transition to the γ -mode were studied experimentally for varying frequencies. It was found that the voltage at the α – γ transition behaves inversely proportional to the applied frequency f and that the corresponding power scales with an f 3/2 law. Both these findings agree well with the results of time-dependent, spatially one-dimensional fluid modelling of the discharge behaviour, where the f 3/2 scaling of the α – γ transition power is additionally verified by the established concept of a critical plasma density for sheath breakdown. Furthermore, phase resolved spectroscopy of the optical emission at 750.39 nm as well as at 810.37 nm and 811.53 nm was applied to analyse the excitation dynamics of the discharge at 27 MHz for different applied powers. The increase of the power leads to an additional maximum in the excitation structure of the 750.39 nm line emission at the α – γ transition point, whereas the emission structure around 811 nm does not change qualitatively. According to the fluid modelling results, this differing behaviour originates from the different population mechanisms of the corresponding energy levels of argon.